PUBLIC EVENTS AS A MEAN OF DESTINATION PROMOTION - Lingeberzins, Eriks (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
Tourism is often considered as a strategic economic development priority not only in areas with high numbers of domestic and international visitors but also in more remote and rural areas. Their ability to attract visitors is often limited by the number and the range of available infrastructure and other tangible and intangible resources. Even defined as development priority, tourism promotion is often underfinanced due to municipality budget priorities and often short-term focus whereas tourism promotion requires long term approaches. Less developed areas are also lacking overall understanding of various tourism impact forms and public officers face challenges communicating tourism marketing spendings to the public. These trends fit under the category of public events as a means of tourism promotion. Two cities qualifying as regional tourism destinations have prioritised public events as tourism promotion priorities. The aim of the research is to explore perception of public events as tourism destination promotion tools in regional tourism destinations. Research is a case study of public events as a means of tourism destination promotion in Bauska and Talsi city. Primary data has been obtained via semi-structured interviews with involved stakeholders representing public and private sector to develop practically applicable recommendations to other tourism destinations.